2023
DOI: 10.3724/abbs.2023058
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical mechanism of erastin-induced ferroptotic cell death in neuronal cells

Abstract: Ferroptosis is a new form of nonapoptotic cell death closely associated with glutathione (GSH) peroxidase 4 inhibition and/or GSH depletion, resulting in the accumulation of cellular iron and lipid peroxides. The exact mechanism by which GSH depletion causes the accumulation of reactive oxygen species (ROS) and lipid-ROS and subsequent ferroptotic cell death in neuronal cells remains unclear. In the present study, using immortalized HT22 mouse hippocampal neuronal cells as a model, we show that nitric oxide (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…It has been reported that ER-induced GSH depletion activated disulfide isomerase (PDI) which induced iNOS, resulting in accumulation of cellular lipid ROS. Hou et al, have also shown that ER-induced GSH depletion leads to activation of PDI, which then mediates ferroptosis by catalyzing nNOS dimerization, resulting in the accumulation of cellular • NO, ROS and lipid ROS which ultimately causes ferroptotic cell death in immortalized HT22 mouse hippocampal neuronal cells [47]. We have also previously reported that • NO-generating drug, NCX4040, induces ferroptosis in colon cancer cells which was further enhanced in the presence of ER [40].…”
Section: Discussionmentioning
confidence: 66%
“…It has been reported that ER-induced GSH depletion activated disulfide isomerase (PDI) which induced iNOS, resulting in accumulation of cellular lipid ROS. Hou et al, have also shown that ER-induced GSH depletion leads to activation of PDI, which then mediates ferroptosis by catalyzing nNOS dimerization, resulting in the accumulation of cellular • NO, ROS and lipid ROS which ultimately causes ferroptotic cell death in immortalized HT22 mouse hippocampal neuronal cells [47]. We have also previously reported that • NO-generating drug, NCX4040, induces ferroptosis in colon cancer cells which was further enhanced in the presence of ER [40].…”
Section: Discussionmentioning
confidence: 66%